New tomato variety Agata Plus for open ground in the south of Russia - B. N. Novikov; L. N. Novikova (Овощи России, 2022)
Relevance. To increase the consumption of tomato and its diversity on the market, it is important to create new varieties that have economically valuable characteristics and are in demand among consumers. The aim of the research was to create a new determinant early-ripening variety of lettuce tomato, plastic, consistently productive, large-fruited, with dense pulp and high taste, tolerant to diseases.Materials and methods. The studies were carried out at the collection site of the Crimean OSS of the VIR branch (Krasnodar Region, Krymsk). The Agata Plus cultivar was obtained by crossing parental forms with subsequent multiple selections against a natural infectious background. As a mother, we used a salad variety of the Russian selection Agata – early maturing, undersized, with an average yield and fruits with good taste and average weight. The paternal form was a hybrid of the Dutch selection F1 Eploz, characterized by early maturity, medium height, medium leafiness, largefruited, dense pulp, consistently high yield and excellent taste of the fruit. The Agata tomato variety included in the State Register of the Russian Federation was taken as a standard.Results. Evaluation of breeding lines for a complex of biological, morphometric, economically valuable traits using individual and mass selections made it possible to obtain the best early ripening form of salad designation, marked by large fruit size, consistently high yield and good taste. In 2017, this form, called Agata Plus, was submitted to the State Variety Test, and since 2020 this variety has been approved for use.